The Tortured Life of Scofield Thayer - Dempsey, James, 1948- (Book collections on Project MUSE., 2014)
Scofield Thayer, as owner of The Dial during the 1920s, was the center of the flow of cultural ideas between the United States and Europe, particularly those of the various modernist movements. This is the first biography of Thayer.